(untitled) (Al-Academy, 2025)
Abstract: The research aims to identify the Metaverse technology, define the field of immersive design and arts, and explore the specializations of the field of immersive design and arts, to answer the research question: What is the possibility of benefiting from the Metaverse technology as an introduction to the development of the field of immersive design and arts? The research followed the descriptive and analytical approach, as the researcher deliberately selected a sample of specializations in the field of immersive design and arts to explore them. The study reached several results, the most prominent of which are: Confirming the importance of the relationship between emerging technological innovations and design and arts in its various specializations. And that the Metaverse technology has caused a digital revolution in the world of design and arts. It has also contributed to enabling three-dimensional embodiment through the avatar identity to support interaction during immersive artistic experiences. Metaverse technology provides opportunities to experiment with new and unconventional immersive artistic practices to explore diverse and unique artistic expressions on an unlimited scale. Metaverse technology can also be used to enable designers and artists to share and interact with others while practicing immersive artistic experiences.